Alveolar Sarcoidosis Mimicking Idiopathic Interstitial Pneumonia Without Mediastinal Lymphadenopathy - Hiroki Kanasaki; Noriyuki Enomoto; Yuko Tanaka; Suguru Kojima; Keisuke Morikawa; Shogo Nakai; Shusuke Yazawa; Yasutaka Mochizuka; Yusuke Inoue; Hideki Yasui; Hironao Hozumi; Yuzo Suzuki; et al. (Respirology Case Reports)
ABSTRACT We present a case of alveolar sarcoidosis showing lower lobe‐predominant areas of airspace consolidation and ground‐glass attenuation on HRCT, mimicking idiopathic interstitial pneumonia (IIP) with spontaneous wandering. Mediastinal lymphadenopathy and uveitis were negative. Surgical lung biopsy revealed multiple non‐necrotising granulomas. Alveolar sarcoidosis that mimics IIP without mediastinal lymphadenopathy is rare.